Bridging Islamic Inheritance Law And Local Traditions: Empirical Insights From Brahu Village - Indah Puspitasari; Ahmad Muqorobin; M. Bagus Saputro (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The implementation of Islamic inheritance law is a religious obligation for every Muslim, as mandated by the Qur’an, Hadith, and the consensus (ijma') of the Prophet’s companions. However, its application often faces obstacles due to limited public understanding, as seen in Brahu Village, Siman Subdistrict, Ponorogo. This study aims to explore the community’s knowledge, practices, and efforts to apply Islamic inheritance law while formulating an educational model suited to local socio-cultural characteristics. Using a qualitative approach through in-depth interviews and observations, the research found that inheritance distribution predominantly follows customary practices based on equal sharing (dum podo). Discussions on inheritance are typically delayed until the 1,000th day after death or longer if a spouse survives. Raising the issue immediately after death is considered culturally inappropriate and contrary to the value of pekewuh (reluctance). Despite this, there is a sincere desire within the community to understand and implement Islamic inheritance principles. Therefore, a gradual, systematic, and community-based educational strategy is needed, utilizing religious gatherings such as Yasinan, Aisyiyah, Fatayat, and mosque caretaker (takmir) training programs. The implementation of Islamic inheritance law can be carried out harmoniously within families, starting with education on fundamental principles such as the obligation to identify heirs and their shares according to Islamic rulings, followed by a distribution process based on mutual agreement when necessary. This approach serves as a bridge that allows Islamic inheritance law and local traditions to coexist.